STUDIES ON ANTIMICROBIAL COMPOUNDS FROM SELECTED MARINE PHYTOPLANKTONS - SELVENDRAN.M. (International Journal of Pharma and Bio Sciences, 2013)
The antimicrobial compounds were extracted from two marine microalgae namely Nanochloropsis oculata and Chaetoceros calcitrans using different organic solvents. The efficiency of those extracts on aquatic pathogens such as Staphylococcus aureus, Pseudomonas aeruginosa, Vibrio harveyi, V. parahaemolyticus and Aeromonas hydrophila. Among the extracts obtained from microalgae, chloroform + methanol (2:1) extract of N. oculata and butanolic extract of C. calcitrans had the maximum inhibiting activity against all tested aquatic pathogens. Most effective crude extracts were again purified by column chromatography and inhibitory activity of the eluted fractions tested against same pathogens. Active fraction was analyzed through FTIR for knowing its functional group. Column purified extracts of antimicrobials obtained from N. oculata was found to be light sensitive compound which was activated at an intensity of 200 lux for 18 h. Analysis on mode of activity showed inhibition of cell wall formation in the pathogen. Identified active functional groups were carboxyl and nitro group in N. oculata and nucleoside compound in C. calcitrans.